2020
DOI: 10.5888/pcd17.200202
|View full text |Cite|
|
Sign up to set email alerts
|

Urban–Rural Disparities in Access to Low-Dose Computed Tomography Lung Cancer Screening in Missouri and Illinois

Abstract: What is already known on this topic? Low-dose computed tomography (LDCT) screening for lung cancer is recommended for current and former smokers meeting eligibility criteria. As of 2017, rural areas generally had less geographic access to LDCT screening than urban areas. What is added by this report? Despite the recent proliferation of LDCT screening, rural areas in Missouri and Illinois have low levels of access to screening. We observed no association between geographic access to screening and lung cancer mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Although these discoveries could benefit everyone, differences in access may widen preexisting cancer care and outcome gaps, leading to negative social consequences. [32][33][34] Therefore, there is an urgent need to transition from describing patterns and associations to implementing and evaluating interventions to mitigate avoidable differences between individuals of different socioeconomic or demographic groups. [23][24][25][32][33][34][35] In the absence of active interventions, health care disparities will continue to worsen, reflecting broader social and economic dynamics.…”
Section: Effect Of Emergent Therapeutics On Health Care Disparitiesmentioning
confidence: 99%
“…Although these discoveries could benefit everyone, differences in access may widen preexisting cancer care and outcome gaps, leading to negative social consequences. [32][33][34] Therefore, there is an urgent need to transition from describing patterns and associations to implementing and evaluating interventions to mitigate avoidable differences between individuals of different socioeconomic or demographic groups. [23][24][25][32][33][34][35] In the absence of active interventions, health care disparities will continue to worsen, reflecting broader social and economic dynamics.…”
Section: Effect Of Emergent Therapeutics On Health Care Disparitiesmentioning
confidence: 99%
“…Expanded Access to Lung Cancer Screening-Implementing Wisely to Optimize Health These subspecialists may be in short supply in lower-resource settings but are necessary to minimize unnecessary invasive testing and to promptly diagnose and treat identified cancers. It is not surprising that rural patients, for example, have disparities in LCS access 15. To scale LCS to even more eligible individuals under the new guidelines[3][4][5] would require considerable investment in CT scanners, radiologists, LCS coordinators, EHR updates-all the many components required to make this intervention effective and efficient.These barriers are not insurmountable.…”
mentioning
confidence: 99%
“…Urban–Rural Disparities in Access to Low-Dose Computed Tomography Lung Cancer Screening in Missouri and Illinois ( 14 )…”
mentioning
confidence: 99%
“…Geographic location continues to be an important contributor in shaping access to timely and necessary screening and treatment options ( 33 ). Rohatgi et al conducted original research examining relationships among rurality, sociodemographic characteristics, and access to low-dose computed tomography (LDCT) screening for lung cancer and screening access and lung cancer mortality ( 14 ). This study revealed that more than 97% of metropolitan residents had access to LCDT screening, compared with just over 40% of nonmetropolitan residents.…”
mentioning
confidence: 99%
See 1 more Smart Citation